ANNOTATIONS IN E-LEARNING - Jindia, Anjali; Chawla, Sonal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Web-based learning has become an important way to enhance learning and teaching, offering many learning opportunities. A limitation of current Web-based learning is the restricted ability of students to personalize and annotate the learning materials. Providing personalized tools and analyzing some types of learning behavior, such as students’ annotation, has attracted attention as a means to enhance Web-based learning. There has been a sharp increase in the volume and quality of electronic publishing on the web in the past few years. Many research journals are going on-line. The advantages of pelectronic publishing are obvious and enormous: instantaneous access to archives, paperless media and fast document search to name a few. However, annotation of documents in electronic form has been surprisingly underdeveloped. Existing word processing software offers some tools for electronic document annotation. But as of today, these annotation features are so modest and limited, that they lose out to the convenient common practice of working with paper versions of documents [1]. The results of a surveys conducted came as no surprise: the absolute majority of researchers and students prefer to print out an electronic paper before reading and annotating it. Our claim is that electronic annotations can not only be as convenient as their paper counterparts, but they are superior in terms of the additional advanced capabilities they can offer. This claim makes the basis of our Annotation Technology (AT). AT is a set of principles that form a foundation for development of advanced and successful electronic annotation systems.